Polyhydroxyalkanoates: Much More than Biodegradable Plastics - López, Nancy Irene (2015)
Bacterial polyhydroxyalkanoates (PHAs) are isotactic polymers that play a critical role incentral metabolism, as they act as dynamic reservoirs of carbon and reducing equivalents.These polymers have a number of technical applications since they exhibit thermoplasticand elastomeric properties, making them attractive as a replacement ofoil-derived materials. PHAs are accumulated under conditions of nutritional imbalance(usually an excess of carbon source with respect to a limiting nutrient, such as nitrogenor phosphorus). The cycle of PHA synthesis and degradation has been recognized as animportant physiological feature when these biochemical pathways were originallydescribed, yet its role in bacterial processes as diverse as global regulation and cell survivalis just starting to be appreciated in full. In the present revision, the complex regulationof PHA synthesis and degradation at the transcriptional, translational, andmetabolic levels are explored by analyzing examples in natural producer bacteria,such as Pseudomonas species, as well as in recombinant Escherichia coli strains. Theecological role of PHAs, together with the interrelations with other polymers and extracellularsubstances, is also discussed, along with their importance in cell survival, resistanceto several types of environmental stress, and planktonic-versus-biofilm lifestyle.Finally, bioremediation and plant growth promotion are presented as examples of environmentalapplications in which PHA accumulation has successfully been exploited.